PEDAGOGICAL FOUNDATIONS FOR THE APPLICATION OF THE AXIOLOGICAL APPROACH IN MODERN HIGHER EDUCATION - Mansurova Nigoraxon Rustamjonovna (Bright Mind Publishing, 2025)
This article explores the pedagogical foundations and practical significance of applying an axiological approach in modern music education, with a focus on preserving and promoting national musical heritage among future teachers. The research highlights the growing necessity of value-based learning strategies to develop students’ cultural awareness, moral responsibility, and aesthetic appreciation. Within the framework of pedagogical axiological theory, the study investigates how integrating value-oriented content into music curricula enhances students’ ability to comprehend, interpret, and carry forward the intellectual and artistic traditions of Uzbek classical and folk music. Drawing upon the rich cultural legacy of Bukhara and the contributions of prominent musicians and educators, the article analyses theoretical insights, ethical and didactic dimensions, and the socio-cultural imperatives of axiological education. Moreover, it provides a philosophical and methodological explanation of key concepts such as “value,” “axiology,” and “cultural continuity,” thereby establishing a strong foundation for incorporating spiritual, moral, and national values into music pedagogy. The findings underscore the importance of axiological thinking for fostering students’ intellectual development and for strengthening the cultural identity and ethical worldview of future music educators.
Keywords: Axiological approach, music education, national heritage, pedagogical values, spiritual development, Bukhara musical tradition, value-based learning, music pedagogy, cultural identity.